2020
DOI: 10.1112/topo.12170
|View full text |Cite
|
Sign up to set email alerts
|

Knot cobordisms, bridge index, and torsion in Floer homology

Abstract: Given a connected cobordism between two knots in the 3-sphere, our main result is an inequality involving torsion orders of the knot Floer homology of the knots, and the number of local maxima and the genus of the cobordism. This has several topological applications: The torsion order gives lower bounds on the bridge index and the band-unlinking number of a knot, the fusion number of a ribbon knot, and the number of minima appearing in a slice disk of a knot. It also gives a lower bound on the number of bands … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…, where Kh t is Lee's perturbation of Khovanov homology. Similar results are obtained in the context of knot Floer homology(see [12] [5]).…”
supporting
confidence: 83%
“…, where Kh t is Lee's perturbation of Khovanov homology. Similar results are obtained in the context of knot Floer homology(see [12] [5]).…”
supporting
confidence: 83%
“…For the torus knot T 2,3 we have br(T 2,3 ) = 2 and it is elementary to see that b(T 2,3 ) = 2. In fact, in [18] it is shown that for torus knots, b(K) = br(K). Yet there are still basic examples that are unresolved: for K = nT 2,3 we have br(K) = n + 1; is it true that b(nT 2,3 ) = n + 1?…”
Section: Problemsmentioning
confidence: 99%
“…Recall that the fusion number Fus(K) of a ribbon knot K in S 3 is the minimal number of bands in a handle decomposition of ribbon concordance C from the unknot U to K in S 3 × [0, 1]. By [JMZ20], the torsion order of K in S 3 provides a lower bound for the fusion number of K. There are a few possible generalizations we will consider.…”
Section: Applicationsmentioning
confidence: 99%
“…Let K be a nullhomologous knot in a 3-manifold Y . Define the torsion order of K in Y to be the quantity [JMZ20] use the the torsion order of knots in S 3 to give bounds on many topological invariants of knots, including the fusion number, the bridge index, and the cobordism distance. We prove an analogue of [JMZ20, Theorem 1.2] in the ribbon homology cobordism setting.…”
Section: Introductionmentioning
confidence: 99%